Study on the Correlation between Chinese Medicine Syndrome and Cognitive Dysfunction in Mild Cognitive Impairment. (24th June 2022) - Lin, Zhiying; Huang, Tianwen; Zheng, Guanyi; Chen, Runqiong; Yao, Minglong; Liu, Wenhong; Li, Shujie
Abstract : Objective . To investigate the correlation between Chinese medicine syndrome and cognitive dysfunction in patients with mild cognitive impairment (MCI). Methods . 121 MCI patients were included for syndrome differentiation and syndrome scoring according to the Chinese medicine syndrome classification standard of senile dementia. The cognitive function and cognitive subitems (including visual space and executive function, naming, attention, language, abstraction, delayed recall, and orientation) of patients with different Chinese medicine syndromes were scored with the Montreal Cognitive Assessment (MoCA). Correlation analysis was made on Chinese medicine syndromes and cognitive domain damage. Results . Chinese medicine syndromes from most to least were kidney deficiency and marrow reduction syndrome, turbid phlegm obstructing orifices syndrome, deficiency of heart and spleen syndrome, qi stagnation and blood stasis syndrome, and yin deficiency of heart and liver syndrome. There were no significant differences in MoCA scores among different Chinese medicine syndromes (P > 0.05 ).In the kidney deficiency and marrow reduction syndrome, the delayed recall score was 1.74 ± 1.23 and the difference was statistically significant when compared with deficiency of heart and spleen syndrome or the yin deficiency of heart and liver syndrome (P < 0.05 ). In the turbid phlegm obstructing orifices syndrome, the delayed recall score was 1.81 ± 1.33 and the difference was statistically significant when compared with the yin deficiency of heart and liver syndrome (P < 0.05 ). There was a significant negative correlation between the kidney deficiency and marrow reduction syndrome's Chinese medicine syndrome scores and MoCA scores (P < 0.01 ), and there was a negative correlation between the turbid phlegm obstructing orifices syndrome's Chinese medicine syndrome scores and MoCA scores (P < 0.05 ). Correlation analysis showed that the kidney deficiency and marrow reduction syndrome was significantly negatively correlated with delayed recall scores (P < 0.01 ), and it was also negatively correlated with visual space and executive function scores (P < 0.05 ). The turbid phlegm obstructing orifices syndrome was significantly negatively correlated with delayed recall scores (P < 0.01 ). Conclusion . The kidney deficiency and marrow reduction syndrome and the turbid phlegm obstructing orifices syndrome were the most common syndromes in MCI. Patients with kidney deficiency and marrow reduction syndrome might have obvious damage in delayed recall function and have damage in visual space and executive function. Patients with turbid phlegm obstructing orifices syndrome might have obvious damage in delayed recall function.